2016
DOI: 10.1039/c6ob01273f
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven electron injection from a biotinylated triarylamine donor to [Ru(diimine)3]2+-labeled streptavidin

Abstract: Electron transfer from a biotinylated electron donor to photochemically generated Ru(iii) complexes covalently anchored to streptavidin is demonstrated by means of time-resolved laser spectroscopy. Through site-selective mutagenesis, a single cysteine residue was engineered at four different positions on streptavidin, and a Ru(ii) tris-diimine complex was then bioconjugated to the exposed cysteines. A biotinylated triarylamine electron donor was added to the Ru(ii)-modified streptavidins to afford dyads locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 53 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…In vitro studies further showed that biot-Ru-SAV mut has a catalytic efficiency 2-fold that of biot-Ru-SAV peri , with increasing kcat and decreasing KM values, respectively. In another study, Wenger, Ward, and co-workers [161] Cu center with an electron transfer function. Together with previous achievements [153], these studies show that the biotin-steptavidin system is well-exploited for design of novel metalloenzymes with diverse functions.…”
Section: In Other Protein Scaffoldsmentioning
confidence: 99%
“…In vitro studies further showed that biot-Ru-SAV mut has a catalytic efficiency 2-fold that of biot-Ru-SAV peri , with increasing kcat and decreasing KM values, respectively. In another study, Wenger, Ward, and co-workers [161] Cu center with an electron transfer function. Together with previous achievements [153], these studies show that the biotin-steptavidin system is well-exploited for design of novel metalloenzymes with diverse functions.…”
Section: In Other Protein Scaffoldsmentioning
confidence: 99%
“…The ruthenium(II) complex [Ru(bpy) 2 (phenNHCOCH 2 Br)](PF 6 ) 2 , the biotinylated supramolecular binding partner triarylamine Biot-TAA,a nd the reference triarylamine TAA-NH 2 were synthesized as previously described (Figure 1). [50] The alkoxy-amine containing methyl viologen analogue aMV 2 + + was synthesized in four steps, as detailed in the Supporting Information (Scheme S1 andF igures S1-S7). As previously demonstrated, [50] the dyad bearing the ruthenium photosensitizer covalently anchored at position K121C of Sav displayed the highest quantum yield of the oxidized Biot-TAA.W et hus selected K121C Sav as as tarting scaffold fora ll mutagenesis studies reported herein.I nspection of the X-ray structure of the mature S112A Sav (pdb code:3 PK2) [54] revealed ad isordered N-terminus (i.e., residues 2-12, ASMTGGQQMGR).…”
Section: Synthesis and Structural Aspectsmentioning
confidence: 99%
“…[50] The alkoxy-amine containing methyl viologen analogue aMV 2 + + was synthesized in four steps, as detailed in the Supporting Information (Scheme S1 andF igures S1-S7). As previously demonstrated, [50] the dyad bearing the ruthenium photosensitizer covalently anchored at position K121C of Sav displayed the highest quantum yield of the oxidized Biot-TAA.W et hus selected K121C Sav as as tarting scaffold fora ll mutagenesis studies reported herein.I nspection of the X-ray structure of the mature S112A Sav (pdb code:3 PK2) [54] revealed ad isordered N-terminus (i.e., residues 2-12, ASMTGGQQMGR). These residues were modeled using Yasara [55] and possesseda na-helicals tructure.…”
Section: Synthesis and Structural Aspectsmentioning
confidence: 99%
See 2 more Smart Citations